Computer-Assisted Corrective Osteotomy of Malunited Pediatric Radial Neck Fractures—Three-Dimensional Postoperative Accuracy and Clinical Outcome. Issue 12 (December 2017) - Weigelt, Lizzy; Fürnstahl, Philipp; Schweizer, Andreas
Abstract : Summary: Neglected or incorrect treatment of pediatric radial neck fractures may lead to symptomatic malunions. Computer-assisted corrective osteotomies with patient-specific guides have been proposed as a promising technique for the reconstruction of malunited long bone deformities. The aim of this study was to evaluate the accuracy and clinical outcome of this technique in children with malunited fractures of the radial neck. Four children [2 boys, 2 girls; mean age 12 (10–16) years] underwent computer-assisted closing wedge osteotomy of the radial neck. The contralateral uninjured side was used as a reconstruction template. Computed tomography were performed 8 weeks postoperatively to confirm bony consolidation and to quantify residual 3D rotational and translational displacement error. Clinical outcome [pain, range of motion (ROM)] and overall satisfaction were documented. Preoperative subluxation of the radial head could be corrected in 2 of 3 patients. One patient had to be revised because of secondary traumatic loss of reduction. At the last follow-up [mean 16 (range, 12–24) months], all patients were pain free for activities of daily living (preoperative pain: visual analog scale 6). Pain during sport activities could be substantially reduced (visual analog scale 8→2). Although the procedure failed to improve ROM, none of the patients had limitations regarding work, daily, or sports activities. Yet, restricted ROM was considered as a cosmetic problem in 1 patient. Full consolidation of the osteotomy site, with no signs of avascular necrosis of the radial head, was achieved in all patients. The deformity could be substantially reduced, from a 3D angle of 13–40 degrees to 3–7 degrees (58%–89% deformity correction). Computer-assisted corrective osteotomy is a novel technique for the treatment of radial neck malunions that led to adequate pain reduction and 3D accuracy of deformity correction in our small case series. Despite the lack of improved ROM, all patients were satisfied and would undergo the same procedure again. Abstract : Supplemental Digital Content is Available in the Text.